Sistem Informasi Monitoring Perkembangan Anak di Sekolah Taman Kanak – kanak Berbasis Cloud - Saputra, Putu Satya; Sukarsa, I Made; Bayupati, I Putu Agung (Lontar Komputer : Jurnal Ilmiah Teknologi Informasi; Vol. 8, No. 2 Agustus 2017DO - 10.24843/LKJITI.2017.v08.i02.p05, 2017)
Education is a means to advance human resources. Achieving educational progress requires a tool for managing data such as curriculum data, students and grades. This tool can be used to control student activities in school so that the results can be delivered immediately and the monitoring process can run effectively because of communication between the school and parents. Child Development Monitoring Information System at Cloud-Based Kindergarten School is a Web-based Software As A Services (SaaS) service. This information system created by using cloud technology provides facilities to perform the management of various academic data such as student data, values and so forth. A cloud-based academic information system service that can be relied on to operate online without servers and installations for every system in school. The use of cloud technology in making this application is expected to further simplify the process of academic data management and school data that is generally done conventionally. The results of research conducted by spreading the questionnaire using Likert scale calculations show more than 50% of users agree with the statement already made.